PIBID/SPANISH: LITERATURE READING, CREATIVITY AND ELEC TEACHING (PERcursos Linguísticos, 2021)
This present work aims to show and discuss the results of one of the practices carried out in the teaching of literary reading in foreign language classes at a kindergarten developed by PIBID Spanish/2018. In order to accomplish that, it was decided to expose in a critical way one of the campaigns developed by the students of group 4 at CEI Criarte kindergarten/UFES by a PIBID scholarship holder. We understand that the different literatures are paramount for language learning, once they reflect the diverse ways of living from the people that produce them. They also offer a great repertoire for world understanding. In addition to this they contribute to the emotional and citizen formation of each individual. This way, our objective is to promote the mediation about playful and contextualized teaching of the foreign literatures in a language kindergarten class. Hence, we highlight a more meaningful teaching, a familiarization with lots of different cultures and our own, as well as with the creativity development and imagination as observed results. As theoretical referential we use Cameron (2001), Almeida Filho (1993) and Schütz (2008) about foreign language teaching for children; Ortega and Clímaco (2018) about spanish literatures teaching; Colomer (2017) about literature reading and Borges and Mozzer (2008) about creativity.